Effect of plastic film mulch on the production of butterhead lettuce cultivars under protected cultivation - Castoldi, R. [UNESP]; Charlo, H. C O [UNESP]; Ito, L. A. [UNESP]; Braz, L. T. [UNESP] (My University, 2008)
The study was performed in a greenhouse with the aim of evaluating the production of butterhead lettuce cultivars with and without plastic film mulch in the summer. The cultivars studied were 'Elisa', 'Lídia', 'Herman' and 'Luísa'. The experimental design was a split plot, in which the main plot was plastic film mulch (with or without black polyethylene film) and the subplots were the cultivars, with three repetitions. The seedlings were grown in Styrofoam trays of 288 cells and transplanted 25 days after seeding in a space of 25 × 25 cm. Harvests were carried out 45 days after transplanting and the following variables were determined: fresh and dry weights of the aerial part, number of leaves per plant, plant height and the longitudinal and transverse diameters of the plant. Significant differences were found only among the cultivars for the characteristics studied, with no cover × cultivar interaction. Fresh weight of the aerial part of 'Lídia' (270.9 g) was greater than that of 'Herman' (142.5 g), but did not differ from those of 'Luísa' (229.8 g) or 'Elisa' (204.8). The dry weight of the aerial part of 'Lídia' (12.4 g) differed statistically only with respect to that of 'Herman' (7.9 g). The cultivars 'Luísa' and 'Elisa' had an aerial part dry weight of 11.4 and 11.2 g, respectively. The number of leaves per plant of the cultivars 'Luísa' (45.1) and 'Elisa' (43.0) was higher than for 'Herman' (24.05), but did not differ from that of the cultivar 'Lídia' (39.5). The mean transverse and longitudinal diameters, as well as the mean height of the plants, showed that 'Lídia', 'Elisa' and 'Luísa' had the greatest values. The cultivars 'Lídia', 'Elisa' and 'Luísa' were the most productive and plastic film mulch had no effect on lettuce production under protected cultivation.
Keywords: Greenhouse; Lactuca sativa; Mulching; Productivity; Lactuca